Epigenetics Is Implicated in the Basis of Gender Incongruence: An Epigenome-Wide Association Analysis - Ramirez, Karla; Fernández, Rosa; Collet, Sarah; Kiyar, Meltem; Delgado-Zayas, Enrique; Gómez-Gil, Esther; Van Den Eynde, Tibbert; T’Sjoen, Guy; Guillamon, Antonio; Mueller, Sven C.; Pásaro, Eduardo (Frontiers in Neuroscience, 2021)
Introduction: The main objective was to carry out a global DNA methylation analysis in a population with gender incongruence before gender-affirming hormone treatment (GAHT), in comparison to a cisgender population. Methods: A global CpG (cytosine-phosphate-guanine) methylation analysis was performed on blood from 16 transgender people before GAHT vs. 16 cisgender people using the Illumina© Infinium Human Methylation 850k BeadChip, after bisulfite conversion. Changes in the DNA methylome in cisgender vs. transgender populations were analyzed with the Partek® Genomics Suite program by a 2-way ANOVA test comparing populations by group and their sex assigned at birth. Results: The principal components analysis (PCA) showed that both populations (cis and trans) differ in the degree of global CpG methylation prior to GAHT. The 2-way ANOVA test showed 71,515 CpGs that passed the criterion FDR p <0.05. Subsequently, in male assigned at birth population we found 87 CpGs that passed both criteria (FDR p<0.05; fold change ≥ ±2) of which 22 were located in islands. The most significant CpGs were related to genes: WDR45B, SLC6A20, NHLH1, PLEKHA5, UBALD1, SLC37A1, ARL6IP1, GRASP and NCOA6. Regarding the female assigned at birth populations, we found 2 CpGs that passed both criteria (FDR p<0.05; fold change ≥ ±2), but none were located in islands. One of these CpGs, related to the MPPED2 gene, is shared by both, trans men and trans women. The enrichment analysis showed that these genes are involved in functions such as negative regulation of gene expression (GO:0010629), central nervous system development (GO:0007417), brain development (GO:0007420), ribonucleotide binding (GO:0032553), and RNA binding (GO:0003723), among others. Strengths & limitations: It is the first time that a global CpG methylation analysis has been carried out in a population with gender incongruence before GAHT. A prospective study before/during GAHT would provide a better understanding of the influence of epigenetics in this process. Conclusion: The main finding of this study is that the cis and trans populations have different global CpG methylation profiles prior to GAHT. Therefore, our results suggest that epigenetics may be involved in the etiology of gender incongruence